Composite Material Sensitive to Volatile Organic Compounds - Lima, Roberto R.; Hernandez, Leonardo F.; Pecoraro, Édison [UNESP]; Rosim-fachini, Estevão; Da Silva, Maria L.P. (Trans Tech Publications, 2012)
This work evaluates fluorinated thin films and their composites for sensor development. Composites were produced using 5 µm starch particles and plasma films obtained from organic fluorinated and silicon compounds reactants. Silicon wafers and aluminum trenches were used as substrates. Film thickness, refractive index and chemical structure were also determined. Scanning electron microscopy shows conformal deposition on aluminum trenches. Films deposited on silicon were exposed to vapor of volatile organic compounds and CV curves were obtained. A qualitative model (FemLab 3.2® program) was proposed for the electronic behavior. These environmentally correct films can be used in electronic devices and preferentially reacted to polar compounds. Nonetheless, due to the difficulty in signal recovery, these films are more effective in one-way sensors, in sub-ppm range.
Keywords: Composite; Electrical characterization; Plasma; Sensitive layer